Optimization of Mesh Size of Gill Nets to Capture Antblygaster sirtn (Walbaum) in Thoothukkudi Coastal Waters, Southeast Coast of India - N., Neethiselvan; D., Jude; B., Sundaramoorthy; P., Gopalakrishnan (Fishery Technology, 2025)
Amblygastar sirm, a lesser sardine, popularly called 'Keeri Meen Chalai' form a notable fishery in Thoothukkudi coastal waters with peak season from September to February. A. sirm are captured in small meshed drift gill nets with the mesh size ranging from 26 mm to 32 mm. The fishery is mainly constituted by the size group 65-210 mm. The present study deals with the optimization of mesh size to capture the commercially significant length group (141-190 mm) and enmeshing pattern of A. sirm in gill nets with various mesh sizes. The optimum mesh size for the commercial exploitation of A. sirm in Thoothukkudi coastal waters is found to be 30.5 mm